IMPLEMENTATION AND IMPACT OF A HALAL FOOD STANDARD: AN EMPIRICAL STUDY OF MALAYSIA - Dian Permata Sari; Irwandi Jaswir; Mohd. Radzi bin Haji Che Daud (Journal of Islamic Monetary Economics and Finance, 2021)
As a Malaysian halal food standard, MS1500 was established to strengthen the Malaysian role in the global halal market. This study aims to identify the factors affecting the implementation of MS1500, its positive impact, and the relationship between its implementation and impact. The food and beverages industry in Malaysia, which already has a halal certificate and halal logo, was chosen as the study population. The covariance-based structural equation modelling (CB-SEM) method was employed, with 212 sample companies. The results show that Perception-On-Implementation, Halal-Control-System-Activity and Owner-Management-Employee-Limitation were the factors affecting the implementation of MS1500. Four positive impacts of its implementation were also found: Trade & Free Movement, Innovation, Clean & Save Production-Process and Consumer & Corporate Image. In addition, it was discovered that the better the implementation of MS 1500, the greater the positive impact that could be achieved by the industry. It was also found that in Malaysia, finance and regulations were not the factors causing limitations in the implementation of the halal food standard. The findings of the study can be used as an input for Malaysian government in planning suitable programmes to promote the implementation of the standard. Moreover, the extent of the positive impacts of the implementation on the industry is expected to encourage all food sectors in Malaysia to apply and fully implement MS1500 in their daily operations.